Biomechanical analysis of the javelin throw at the 2009 IAAF World Championships in athletics - Lehmann, F. (New Studies in Athletics, 2010)
The techniques of the finalists in the men`s and women`s javelin throw at the 2009 World Championships in Athletics were studied by a team of researchers from the Institute for Applied Training Science in Leipzig, Germany with the aim of obtaining the latest data and insight into the technical condition of the world`s current best throwers.